2021
DOI: 10.1002/rrq.406
|View full text |Cite
|
Sign up to set email alerts
|

What Matters Most? Toward a Robust and Socially Just Science of Reading

Abstract: Science of reading is a term that has been used variously, but its use within research, policy, and the press has tended to share one important commonality: an intensive focus on assessed reading proficiency as the primary goal of reading instruction. Although well intentioned, this focus directs attention toward a problematically narrow slice of reading. In this article, we propose a different framework for the science of reading, one that draws on existing literacy research in ways that could broaden and dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 197 publications
(241 reference statements)
0
18
0
Order By: Relevance
“…I am reminded of Katie's observation about undifferentiated phonics instruction. Inviting her to share this observation with her peers could have prompted critical discussions about how phonics programs are being used in classrooms, why certain programs are adopted, how district-level policies regarding intensive phonics instruction are made (Johnston & Scanlon, 2020), and how these decisions can translate to inequitable classroom practices (Aukerman & Chambers Schuldt, 2021; Hoffman et al, 2020; Willis, 2019). Additionally, we could have debated Katie's suggestion to have some students engage in phonics work while their more phonetically developed peers read silently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…I am reminded of Katie's observation about undifferentiated phonics instruction. Inviting her to share this observation with her peers could have prompted critical discussions about how phonics programs are being used in classrooms, why certain programs are adopted, how district-level policies regarding intensive phonics instruction are made (Johnston & Scanlon, 2020), and how these decisions can translate to inequitable classroom practices (Aukerman & Chambers Schuldt, 2021; Hoffman et al, 2020; Willis, 2019). Additionally, we could have debated Katie's suggestion to have some students engage in phonics work while their more phonetically developed peers read silently.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is a need to show candidates how the literacy profession privileges whiteness and positions the languages and literacies of BIPOC communities pathologically. For instance, it would be essential to examine how a simple view of reading is encased in the TEP and in schools (Aukerman & Chambers Schuldt, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that effective readers are engaged, motivated, and exhibit self‐efficacy; these literate dispositions, as Aukerman and Schuldt (2021) call them, have been shown to positively impact overall reading performance (see Finn & Zimmer, 2012; Schunk, 1989; Unrau et al, 2018). Engaged readers, for example, participate actively and deeply in reading and reading‐related activities; they are attentive, emotionally invested, and care about their interactions with a text's ideas (Aukerman & Schuldt, 2021). Cultivating these dispositions is critical not only to students' developing reading competencies, but also to their evolving literate and academic identities.…”
Section: The Challenges Of Adolescent Literacymentioning
confidence: 99%
“…School-based researchers' field notes reported three main positives related to student learning. During interviews, teachers recounted stories related to improvements in students' motivation to read and their literate dispositions (Aukerman & Schuldt, 2021). One teacher's response exemplified the experiences of others.…”
Section: What Did Ballycook Teachers Think About Pwr?mentioning
confidence: 99%